2020
DOI: 10.1016/j.ijid.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of meningococcal isolates in Tunis, Tunisia: High diversity and impact on vaccination strategies

Abstract: The aim of this study was to characterize Neisseria meningitidis (Men) isolates in Tunisian paediatric patients with invasive meningococcal disease (IMD) in order to target therapeutic and preventive strategies. Methods: Fifty-nine isolates of Men and four cerebrospinal fluid samples that were culture-negative but Men-positive by PCR (NC-MenPPCR) (2009-2016) were collected from IMD patients. Isolates were analysed for their antimicrobial susceptibility. Whole-genome sequencing (WGS) was used to characterize is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
(50 reference statements)
5
12
0
Order By: Relevance
“…Comparable results have been reported by several studies, in Algeria, more than 46 % of the cases affected the age group of less than 10 years old [12]. In addition, in Tunisia, IMDs mainly affect infants at 44.6 % [13]. In the USA, the incidence of the disease is higher in the age group between 1 and 4 years [14].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Comparable results have been reported by several studies, in Algeria, more than 46 % of the cases affected the age group of less than 10 years old [12]. In addition, in Tunisia, IMDs mainly affect infants at 44.6 % [13]. In the USA, the incidence of the disease is higher in the age group between 1 and 4 years [14].…”
Section: Discussionsupporting
confidence: 59%
“…Serogroup W appears to have increased worldwide since 2013 [26]. In the Maghreb region, serogroup W represents in Tunisia a prevalence of 1.6 % [13] and 14 % in Algeria between 1992 and 2013 [19]. In France, 9 % of isolates are due to this serogroup [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,33,37 Despite efforts in Algeria, data on current serogroup distribution remain limited, aside from studies on the outbreak-causing MenW clone. 20 A recent study conducted in Tunisia 39 From the limited available data, N. meningitidis appears to be one of the most common causes of bacterial meningitis across North Africa, identified as the second or third most frequent cause of bacterial meningitis cases in Tunisia, following S. pneumoniae and H. influenzae. 23,24 Studies from Egypt identified N. meningitidis as the most common pathogen causing meningitis and had the highest CFR compared with other pathogens.…”
Section: Discussionmentioning
confidence: 99%